THE ROLE OF THE GALUNGGUNG MUSEUM IN PROMOTING HISTORY LEARNING AND PRESERVING LOCAL CULTURE IN TASIKMALAYA (2020–2024): Peran Museum Galunggung Dalam Upaya Pembelajaran Sejarah dan Pelestarian Budaya Lokal Di Tasikmalaya (2020-2024) - Moch Azka Shohibul Musyaffa; Samsudin; Yasmina Wikan Astri (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Studies on museums in Indonesia have generally emphasized their function either as educational media or as institutions for cultural preservation. However, limited attention has been given to local community-based museums that simultaneously operate as spaces for historical learning and for the preservation of local cultural identity. In the context of Tasikmalaya, the Galunggung Museum presents an important case for examining how a local museum responds to the weakening of public historical awareness amid social and cultural change. This study aims to analyze the historical background of the establishment of the Galunggung Museum and to examine its role in promoting history learning and preserving local culture in Tasikmalaya during 2020–2024. This research employs the historical method, including heuristics, source criticism, interpretation, and historiography. The findings show that the Galunggung Museum functions not merely as a place for storing historical objects, but as a community-based educational and cultural institution. In history learning, the museum contributes through artifact preservation, historical narration, and student visits that enable contextual learning based on material evidence. In cultural preservation, the museum sustains both tangible and intangible local culture through artifact collection, ritual activities, traditional arts, and collaboration with local communities. Nevertheless, its role remains constrained by limited infrastructure, accessibility, promotion, and conservation expertise. This study contributes to the historiography of local museums by showing that a community-based museum can serve simultaneously as a site of historical knowledge production, cultural transmission, and local identity reinforcement. It also expands discussions on the role of non-state museums in preserving local history and culture in contemporary Indonesia.